Lycopene supplementation: effects on oxidative stress, sex hormones, gonads and thyroid tissue in tilapia Oreochromis niloticus during Harness® exposure - Ismail, Rania F.; Hamed, Mohamed; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2023)
Harness® is a commercial herbicide that contains acetochlor at a concentration of 84% as an active ingredient. Ubiquitous, persistent, and substantial uses of Harness® in agricultural processes have resulted in the pollution of nearby water sources, posing a threat to various aquatic biotas, including fish. The effects of Harness® toxicity on fish health are little known. So, this study aimed to describe the impact of herbicide Harness® on the oxidative stress and reproductive and thyroid performance of male and female tilapia (Oreochromis niloticus) and also investigate the prospective role of the natural antioxidant lycopene supplementation in dismissing the adverse properties of Harness®. Antioxidant enzyme (catalase, superoxide dismutase, and total antioxidant capacity) and hormone measurements (T, E2, T3, and T4) were carried out, and gonadal and thyroid follicle histological sections were examined as a method to investigate the effects of Harness® toxicity on fish. Male and female tilapia were exposed to 10 μmol/L and 100 μmol/L of Harness® and treated with 10 mg lycopene/kg for 15 days of exposure. Our results demonstrated that the antioxidant enzyme activity was altered by Harness exposure and serum T for both males and females dropped; also, female E2 levels decreased, but male E2 increased. Exposure to higher dose of Harness® induced elevation in both T3 and T4 levels, although the low exposure dose stimulated T4 levels. Harness® exposure prompted histological variations and degenerative changes in testicular, ovarian, and thyroid follicle tissues. Lycopene supplement administration diminished oxidative stress induced by Harness®, alleviating its endocrine disparaging effects by neutralizing T3, T4, T, and E2 and ameliorating the histological structure of gonadal and thyroid tissues. In conclusion, lycopene supplementation was preformed to normalize the alterations and oxidative damage caused by Harness® in Nile tilapia, suggesting that lycopene-supplemented diet functioned as potent antioxidants and had the ability to alleviate oxidative stress and thyroid and reproductive toxicity caused by herbicide Harness®. Moreover, it is crucial to take appropriate care when consuming herbicides to defend the aquatic environment.